Invisible treasures: Assessing Indonesia’s unique agrobiodiversity for food and nutrition security - Borelli, Teresa; Keim, Ary; Sujarwo, Wawan; Koostanto, Haryanti; Pawera, Lukas; Gullotta, Gaia; Jalonen, Riina; Lombardo, Amea; Hunter, Danny (MDPI, 2024)
Indonesia is a biodiversity hotspot with high levels of endemism of globally important food crops and their crop wild relatives, as well as locally adapted cultivars. This rich diversity is essential to Indonesia’s food and nutrition security, while underpinning the livelihood strategies of small-scale farmers (both men and women) and traditional communities, who act as guardians of this genetic heritage. However, many of Indonesia’s plant genetic resources for food and agriculture are experiencing genetic erosion due to increased crop uniformity and the reduced use and demand for local varieties. Changes in food preferences and consumption patterns have driven the species into agricultural neglect with only some smallholder farmers cultivating the species for cultural reasons. These problems are exacerbated by land-use changes and climate variability. Recognizing the imperative to conserve agrobiodiversity in the region to ensure future food security and sustain livelihoods, the status of conservation and sustainable use of taro, yams, cloves and nutmeg in three target provinces in Indonesia was assessed. Mixed-method analyses were used to document existing conservation efforts and what is currently known of these target crops’ conservation status, both in ex situ collections and in the field, to identify unique biodiversity, as well as the barriers and knowledge gaps on how to better conserve and use this unique genetic diversity for future generations.